Prospects of Development of Domestic Engineering-Pedagogical Education in the Context of European Integration Processes - Bilyk, Viktoria (Pedagogical Discourse, 2012)
Сharacteristic of the status and main directions of development of higher professional education in conditions of Eurointegration processes is offered. The problems and ways of reforming of modern engineering-pedagogical education are studied.